Model Space Time Autoregressive (STAR) dan Aplikasinya Terhadap Penyakit Demam Berdarah Dengue di Provinsi Sulawesi Barat - Wahidah Sanusi; Maya Sari Wahyuni; Rahmat Setiawan (Journal of Mathematics, Computations and Statistics, 2018)
The Space Time Autoregressive (STAR) model is a time series data that has a link between locations (space time). The purpose of this study was to obtain a STAR model that was in accordance with the data on the number of dengue fever patients in West Sulawesi Province and also the forecast data for the next few months. Data in the form of DHF data in five locations, namely Mamuju City, Majene Regency, Polmas District, Central Mamuju Regency, and North Mamuju Regency from January 2014 to July 2016. STAR Estimation parameter model uses vertical squares (MKT) method. The STAR model that matches the data on the number of DHF patients in West Sulawesi Province is the STAR5 model (11). The weighting is a uniform location. In the estimator checking results using uniform location weight of three models. Things that happen between others. Forecast results with the STAR5 (11) model on the number of dengue fever patients in West Sulawesi Province for the next two months, namely August to September 2016, namely 9 people for Mamuju City and 12 people for Polman Regency.